Atypical Histopathological Aspects of Common Types of Lung Cancer—Our Experience and Literature Review - Angela-Ștefania Marghescu; Diana Gabriela Leonte; Alexandru Daniel Radu; Elena Doina Măgheran; Adrian Vasilică Tudor; Cristina Teleagă; Mirela Țigău; Livia Georgescu; Mariana Costache (Medicina, 2024)
Lung cancer is among the most common oncological diseases regarding incidence and mortality, with most of these having epithelial origins. Pathological reporting of these tumors is conducted according to the 5th edition of the World Health Organisation (WHO) classification of thoracic tumours. This study aims to draw the pathologist’s attention to four rare, atypical microscopic aspects that some of the most common types of lung malignancies reveal upon standard evaluation (hematoxylin-eosin stain) that make histopathological diagnosis challenging: acantholytic, pseudoangiosarcomatous, signet ring cell, and clear cell features. Each of these aspects was exemplified by a case diagnosed in the pathology department of the “Marius Nasta” Institute. Furthermore, we analyzed the classification dynamics of different WHO editions and used PubMed to review articles written in English and published in the last eleven years on this subject. Pathologists should be familiar with these unusual aspects to avoid misdiagnoses and to ensure the correct classification of tumors, which is extremely important because these tumor phenotypes have been associated with specific molecular alterations and a worse clinical evolution. There is a need to clarify the histogenesis and associated genetic mutations, given the fact that the rarity of these tumor phenotypes makes their study difficult. Some authors consider these to be overlapping entities; however, we do not encourage this, as they may exhibit different prognoses and various molecular alterations with important therapeutic implications. The signet ring cell feature was associated with ALK rearrangement in lung adenocarcinoma; thus, these patients can benefit from tailored therapy with ALK-tyrosine kinase inhibitors (ALK-TKI). Recent studies associated clear cell morphology with FGFR3-TACC3 fusion, suggesting that patients with this diagnosis may be potentially eligible for FGFR inhibitors. We described, for the first time, the pseudoangiosarcomatous pattern in a case of lung adenocarcinoma; to our knowledge this aspect has only been described until now in the context of squamous cell carcinomas.